PERILAKU BURUNG MALEO (Macrocephalon maleo) DEWASA DI PENANGKARAN KAWASAN TAMAN NASIONAL BOGANI NANI WARTABONE - Faldi Suhendro Gonibala; Martina A. Langi; Wawan Nurmawan (Universitas Sam Ratulangi, 2021)
ABSTRACTThis study aims to study the daily behavior of adult maleo birds in captivity in the Bogani NaniWartabone National Park area. This research was conducted in December 2019. There were 6maleo birds observed consisting of 3 males and 3 females who were placed in cages covering anarea of 20x25 m2. Observations of maleo bird daily behavior were carried out for two weeks,starting at 05.30-10.00 in the morning at 12.00-14.00 and in the afternoon at 15.00-18.00observations were made directly. Each maleo bird behavior included in the observation variablewas observed at time and duration (hours). The results of this study indicate that maleo birds arediurnal birds where the behavior of maleo birds in captivity is social behavior 68.54% morningand afternoon eating behavior 20.16% and resting behavior 11.30% and behavior of femalemaleo birds in captivity. In captivity, social behavior is often done 70.20%, while eatingbehavior in the morning and afternoon is 18.30% and resting behavior is done by maleo birds atnoon and 11.50% in the afternoon.Keywords: Maleo, Daily Behavior, Bogani Nani Wartabone National Park.